2014
DOI: 10.1007/s00266-013-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mammaplasty: Outcome Analysis Based on Bodyweight

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…For preliminary exploration, the change in mean BMI was examined at each follow-up time, using 1-week post-operative Similar results have been reported by Pauzenberger et al [10]. In this study, only 50 women were retrospectively studied.…”
Section: Resultssupporting
confidence: 57%
“…For preliminary exploration, the change in mean BMI was examined at each follow-up time, using 1-week post-operative Similar results have been reported by Pauzenberger et al [10]. In this study, only 50 women were retrospectively studied.…”
Section: Resultssupporting
confidence: 57%
“…However, there were a few studies that looked at the incidence of specific complications following reduction mammaplasty such as infection, thromboembolic events, fat necrosis, hematoma, or seroma formation, in which there was no increased incidence in smokers. 36,39,47,48,[51][52][53] Overall, moderate quality evidence was found to support the recommendation (moderate strength) that patients should be informed preoperatively of the increased risks of complications including infection, T-junction necrosis, and wound complications with simultaneous smoking and reduction mammaplasty. These studies showed increased odds of complications from two to five times the risk compared to nonsmokers.…”
Section: Rationalementioning
confidence: 97%
“…Breast hypertrophy is an important clinical problem that causes neck and back pain, intertrigo underneath the breast folds, and restricts physical activities [ 1 ]. It can also be seen as a source of embarrassment by patients.…”
Section: Introductionmentioning
confidence: 99%